PENINGKATAN KEPEDULIAN LINGKUNGAN MASYARAKAT DENGAN PENDEKATAN REUSE, REDUCE DAN RECYCLE MELALUI PRINSIP THINK GLOBALLY AND ACT LOCALLY DI RT.01 RW.01 DS. DADAPREJO KOTA BATU - Kusuma, Hendra (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2016)
Waste management by the community to be thesolution the problem of household waste. Startingfrom household waste is not treated properly andcorrectly so that the waste is considered as goodsthat do not have economic benefits. Proper wastemanagement can bring benefits to the environmentand can add to the household income through theresults if the waste in the form of fertilizer and itsderivatives. Implementation of the service isimplemented through several stages: planning,outreach and manufacture decomposer. To push ofcom-munities to manage waste properly, it needed anintegrated waste management system within thescope of the neighborhoods where the results of themanagement of such waste can be used as fertilizerthat can be utilized alone or sale. The results of theimplementation of this devotion are the formationdecomposer that can be used by communi